A customer value satisfaction, and loyalty perspective of mobile payment app. - Tien Thao Cong Phan; Tri Quan Dang; Nguyen Thanh Luan (Proceedings The International Conference on Business Based on Digital Platform (BDP-3), 2023)
Although the mobile payment application is very popular and spread all over the world, however, in the increasingly competitive market economy, its market dominance has been affected. To achieve a sustainable competitive advantage, a model has been studied on the views of customer value, satisfaction and loyalty towards mobile payment applications. Based on data analysis of 303 app users, we found that usage intent is a key to driving customer satisfaction and loyalty for mobile payment apps. The findings show that perceived usefulness, perceived ease of use, social influence, quality of service and attitude towards using, thereby driving user intention to use for mobile payment applications. The study provides theoretical insights and practical implications for the field of mobile payment services.
Keywords: 330; Perceived Usefulness; Perceived Ease of Use; Social influence; Quality of service; Attitude Toward Using